(4x/3)+5-3=(3x/2)-1

Simple and best practice solution for (4x/3)+5-3=(3x/2)-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4x/3)+5-3=(3x/2)-1 equation:


x in (-oo:+oo)

(4*x)/3-3+5 = (3*x)/2-1 // - (3*x)/2-1

(4*x)/3-((3*x)/2)-3+1+5 = 0

(4*x)/3+(-3/2)*x-3+1+5 = 0

3-1/6*x = 0 // - 3

-1/6*x = -3 // : -1/6

x = -3/(-1/6)

x = 18

x = 18

See similar equations:

| 4y+6+2y=-12 | | 5(4x-7)=5(-3+8x) | | -2.5b+2.3=-2b+2.4 | | (7/6+17/10+23/15)*t=440 | | -9+15= | | 13y=32y-12 | | 10+9-3=6*5 | | 3/7x+5=-8/7 | | 3=8-3/4k | | P(x)=x^2+5x-6 | | 6x-2=4-10+2x | | 4x-5=2x+8+2x | | 1/2b-3=5/2 | | 156+52h=312 | | 11+2x=x^2 | | 4(x+3)=4(x-9)+3x | | 152+52h=312 | | 25/n=5/8 | | 3x^2+18x+32=5 | | 42=5.25h | | 12+12(x+5)=6(x+8) | | y-7=75 | | f(n)=3n+2 | | g(x)=4x+2 | | 4x-3+2x+21=60x | | 2+2x+3(2x)=99 | | 2(3y+3)-6y=12 | | 18y^2+63= | | 3x-5(x-3)=-4+2x-13 | | -3.7x=57.72 | | Y=2(18/5)-6 | | 2(18/5)-6 |

Equations solver categories